2021
DOI: 10.1177/20503121211030837
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical characteristics and outcomes between alcohol-induced and gallstone-induced acute pancreatitis: An Australian retrospective observational study

Abstract: Objectives: To compare the characteristics and outcomes of patients presenting to hospital with alcohol-induced and gallstone-induced acute pancreatitis. Methods: Retrospective study of all patients with alcohol-induced or gallstone-induced pancreatitis during the period 1 June 2012 to 31 May 2016. The primary outcome measure was hospital mortality. Secondary outcome measures included hospital length of stay, requirements for intensive care unit admission, intensive care unit mortality, mechanical ventilation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…6 In this study, the patient's age range was17 to 90 years with the mean age of presentation being 49.03 years. Yadav et al, Das et al, and Reid et al showed a maximum age of 80 years while Alkareemy et al, showed…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…6 In this study, the patient's age range was17 to 90 years with the mean age of presentation being 49.03 years. Yadav et al, Das et al, and Reid et al showed a maximum age of 80 years while Alkareemy et al, showed…”
mentioning
confidence: 80%
“…Nearly 80% of cases of acute pancreatitis worldwide are caused by gallstone obstruction and alcohol intake. 6 Other factors, such as hypertriglyceridemia and drugs, account for the remaining portion. The variation in demographic and socio-economic factors has been linked with the etiology and severity of acute pancreatitis.…”
mentioning
confidence: 99%
“…More recently, Australian data from 642 consecutive patients with AP found 51% were due to gallstones and 49% due to alcohol. 3 This current study has used AIHW data based on ICD-10-AM coding, which has its own limitations. Specifically, 'Unspecified' AP may be an umbrella code for several aetiologies including autoimmune, viral, hypertriglyceridemia, traumatic, and post ERCP.…”
mentioning
confidence: 99%
“…There are limited epidemiological studies on the incidence of acute and chronic pancreatitis in Australia and New Zealand, with many retrospective cohort studies performed across Australasia evaluating the severity and management of AP rather than its incidence. [3][4][5] While demographic data from these studies can be extrapolated, formal epidemiological data are often lacking. This study is the largest population based study performed of its kind in the region, highlighting the rising incidence of AP across Australia.…”
mentioning
confidence: 99%
See 1 more Smart Citation